2021
DOI: 10.3390/life11010034
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Impairment among Patients with Hidradenitis Suppurativa: A Cross-Sectional Study of 1795 Patients

Abstract: The chronic, inflammatory skin disorder hidradenitis suppurativa (HS) is associated well documented negative influences on patients’ quality of life (QoL). The aim of this study was to present more robust data on patients’ QoL impairment by demographic data and its correlation with well-known HS risk factors on a cohort of 1795 German patients. The instrument used for measuring QoL in this study was the Dermatology Life Quality Index (DLQI). Overall, patients reported a very large effect of HS on their QoL (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 47 publications
8
51
0
4
Order By: Relevance
“…Jemec et al and Matusiak et al also determined that QoL impairment clearly correlates with the severity of skin alterations including the number of lesions (20,22), a fact that was confirmed by further studies (43)(44)(45) and was also observed in our study involving a large patient cohort. In this context, a very recently published study showed a positive correlation of QoL impairment with IHS4 (42). Moreover, we also found that anogenital localization of HS skin alterations has a substantial negative impact on QoL, an observation that was very recently published by Jørgensen et al (45).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Jemec et al and Matusiak et al also determined that QoL impairment clearly correlates with the severity of skin alterations including the number of lesions (20,22), a fact that was confirmed by further studies (43)(44)(45) and was also observed in our study involving a large patient cohort. In this context, a very recently published study showed a positive correlation of QoL impairment with IHS4 (42). Moreover, we also found that anogenital localization of HS skin alterations has a substantial negative impact on QoL, an observation that was very recently published by Jørgensen et al (45).…”
Section: Discussionsupporting
confidence: 84%
“…Jemec et al noted that the highest proportion of physical disability resulted from the soreness and pain induced by HS (20). In fact, the presence of pain but not odor seems to be a crucial contributor to QoL impairment (39,40), and pain severity correlated significantly with DLQI (41,42). Moreover, embarrassment and diminished self-consciousness led to a considerable extent of QoL impairment in our patient cohort.…”
Section: Discussionmentioning
confidence: 57%
“…Other reasons for exclusion along with the flow chart are shown in Figure 1 . Finally, 17 studies, representing 4929 patients with HS, met the eligible criteria and were included and fully reviewed [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies evaluated the impact of pain in the QoL of HS patients, including 4216 participants with a mean age of 35.62 years ( Table 2 ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Visual technology, such as standardised photography, ultrasound and thermography [ 9 , 10 , 11 , 12 ], together with digital technology for patient outcome measures, such as daily digital assessment of pain [ 13 ], have the potential to markedly improve the objective evaluation of HS severity assessment. On the other hand, HS continues to be the skin disease that causes the greatest impairment of quality of life (QoL) [ 14 ] and methods to measure this impairment, although developing, have not yet improved to the extent of other physical aspects of the disease [ 15 , 16 ]. It is likely that many studies on the QoL impact of HS will continue to be carried out: their rate of publication increased from 0–1 per year in the 1990s to 90 in 2019 (PubMed; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%